The Communist party - Phelps, Christopher (Cambridge University Press, 2017)
In the Great Depression, numerous American writers and intellectuals were attracted to the Communist Party of the United States of America (CPUSA). This chapter provides an institutional analysis of that political-literary experience, arguing that it is best understood through a prism of structure.